2021
DOI: 10.7554/elife.61077
|View full text |Cite
|
Sign up to set email alerts
|

Signed and unsigned reward prediction errors dynamically enhance learning and memory

Abstract: Memory helps guide behavior, but which experiences from the past are prioritized? Classic models of learning posit that events associated with unpredictable outcomes as well as, paradoxically, predictable outcomes, deploy more attention and learning for those events. Here, we test reinforcement learning and subsequent memory for those events, and treat signed and unsigned reward prediction errors (RPEs), experienced at the reward-predictive cue or reward outcome, as drivers of these two seemingly contradictory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 63 publications
9
94
1
Order By: Relevance
“…These results suggest that memories about specific rewarding events are successfully encoded and then subsequently reactivated upon a second encounter, consistent with the idea of evidence arising from discrete packets, and with an evaluation function that is predicated on the value experienced in that previous episode, rather than one computed anew. However, these data could also be consistent with separate effects of positive reward prediction errors on choice and memory (Jang et al, 2019;Rouhani & Niv, 2021) . The question of whether memory sampling requires explicit recollection at the time of choice remains an area of active interest.…”
Section: Memory In Actionsupporting
confidence: 66%
“…These results suggest that memories about specific rewarding events are successfully encoded and then subsequently reactivated upon a second encounter, consistent with the idea of evidence arising from discrete packets, and with an evaluation function that is predicated on the value experienced in that previous episode, rather than one computed anew. However, these data could also be consistent with separate effects of positive reward prediction errors on choice and memory (Jang et al, 2019;Rouhani & Niv, 2021) . The question of whether memory sampling requires explicit recollection at the time of choice remains an area of active interest.…”
Section: Memory In Actionsupporting
confidence: 66%
“…Although speculative, it is possible that when a given scene activated the “wrong” object association (at LR-1), this actively triggered a correction in favor of the target object association that supported learning. This account is consistent with evidence that prediction errors can powerfully drive episodic memory 45 , 46 as well as differentiation of hippocampal activity patterns 19 . More broadly—and consistent with our findings, in general—prediction errors may induce abrupt state changes in the hippocampus that facilitate the separation of episodic memories 47 .…”
Section: Discussionsupporting
confidence: 88%
“…Antony et al, 2021 showed that a similar measure of surprise plays a role in the segmentation of memory and correlates with pupil dilation and the activity of dopamine-related regions of the brain in fMRI. The influence of surprise on memory has also been studied in reward-driven experiments where it has been shown that high unsigned reward prediction errors increase the memorability of task-independent stimuli (Rouhani & Niv, 2021;Rouhani et al, 2018); in such settings, reward can be defined as a component of the observation y t , and the unsigned reward prediction error can be seen as the absolute error surprise (c.f. Eq.…”
Section: A Brief Review Of Experimental Resultsmentioning
confidence: 99%
“…(Gottlieb & Oudeyer, 2018), 'how can we formulate other surprise theories like Palm's theory of surprise (Palm, 2012) or the theory of surprise as a compression measure (Schmidhuber, 2010) in our mathematical framework? ', and 'how do different surprise measures contribute to formation (Rouhani & Niv, 2021), segmentation (Antony et al, 2021;Rouhani et al, 2020), and modification (Gershman et al, 2017;Sinclair & Barense, 2018) of memory? '.…”
Section: Discussionmentioning
confidence: 99%